Two-dimensional heterostructure quasi-BIC photonic crystal surface-emitting laser with low divergence - Tang Renjie; Shi Yilin; Shang Hongpeng; Wu Jianghong; Ma Hui; Wei Maoliang; Luo Ye; Chen Zequn; Ye Yuting; Jian Jialing; Zheng Xiaorui; Lin Hongtao; et al. (Nanophotonics)
High beam quality, large-area output, and small footprint are significant pursuing goals for vertical-cavity surface-emitting lasers (VCSELs), which impose strict requirements on tight light confinements with minimized radiation losses. To achieve this, bound states in the continuum (BICs) have been demonstrated as an effective way of trapping light. Here, we combine BICs and photonic bandgaps to realize a quasi-BIC single-mode photonic crystal (PhC) laser on a colloidal quantum dots (CQDs)/silicon oxide (SiO2) hybrid integrated platform. The PhC cavity is a defect-free hexagonal heterostructure with three regions, and the thin CQDs film is embedded within the SiO2 nanopillar planar array as both an optical gain material and a backbone for the PhC. The mode gaps between different regions provide the lateral confinement while the quasi-BICs near the Γ-point generate the small-divergence vertical radiation coupling, resulting in a well-defined emission concentrating within ±1.85° of the normal surface direction and an optical pumping energy density threshold of 216.75 μJ/cm2. Our results demonstrate the design flexibility and versatility of the quasi-BIC laser even with a low contrast of a refractive index between the PhC slab and the substrate, which has potential applications in cavity quantum electrodynamics, nonlinear optics, and integrated photonics.